Occupational Sharp Injury and Splash Exposure among Healthcare Workers in a Tertiary Hospital - Mathew, Roshan; Mohindra, Ritin; Sahu, Ankit; Bhat, Rachana; Ramaswami, Akshaya; Aggarwal, Praveen (Journal of Laboratory Physicians, 2021)
Background Occupational hazards like sharp injury and splash exposure (SISE) are frequently encountered in health-care settings. The adoption of standard precautions by healthcare workers (HCWs) has led to significant reduction in the incidence of such injuries, still SISE continues to pose a serious threat to certain groups of HCWs.Materials and Methods This was a retrospective study which examined the available records of all patients from January 2015 to August 2019 who self-reported to our emergency department with history of sharp injury and/or splash exposure. Details of the patients, mechanism of injury, the circumstances leading to the injury, status of the source (hepatitis B surface antigen, human immunodeficiency virus, and hepatitis C virus antibody status), and the postexposure prophylaxis given were recorded and analyzed. Data were represented in frequency and percentages.Results During the defined period, a total of 834 HCWs reported with SISE, out of which 44.6% were doctors. Majority of the patients have SISE while performing medical procedures on patients (49.5%), while 19.2% were exposed during segregation of waste. The frequency of needle stick injury during cannulation, sampling, and recapping of needle were higher in emergency department than in wards. More than 80% of HCWs received hepatitis B vaccine and immunoglobulin postexposure.Conclusion There is need for periodical briefings on practices of sharp handling as well as re-emphasizing the use of personal protective equipment while performing procedures.
Keywords: needle stick injury; healthcare workers; occupational hazards; postexposure prophylaxis